2021
DOI: 10.12659/msm.932410
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Traditional Versus Conservative Endodontic Access Cavities Design of the Maxillary First Molar: Using Cone-Beam Computed Tomography

Abstract: Background This study aimed to compare the size and location of the traditional and conservative endodontic access cavities of the right maxillary first molar teeth, projected on the occlusal surface using cone-beam computed tomography (CBCT), to obtain an ideal access cavity. Material/Methods Five hundred CBCT images of the right maxillary first molars, including 198 males and 302 females, were retrospectively evaluated using KaVo eXam Vision software. First, a rectang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Cone beam computed tomography (CBCT) is a relatively new imaging techique that shows 3D images of structures. CBCT scanning can be useful in endodontics for detecting AP, assesing root canal morphology, detecting procedural errors, and evaluating postoperative healing outcomes [ 5 , 6 ]. Estrela et al [ 7 ] evaluated a new periapical index (PAI) based on CBCT for the identification of AP.…”
Section: Introductionmentioning
confidence: 99%
“…Cone beam computed tomography (CBCT) is a relatively new imaging techique that shows 3D images of structures. CBCT scanning can be useful in endodontics for detecting AP, assesing root canal morphology, detecting procedural errors, and evaluating postoperative healing outcomes [ 5 , 6 ]. Estrela et al [ 7 ] evaluated a new periapical index (PAI) based on CBCT for the identification of AP.…”
Section: Introductionmentioning
confidence: 99%
“…Access cavity preparation is usually set up by projecting the outline, including the pulp horn and root canal orifice, onto the occlusal plane to establish the cavity. This is appropriate for permanent teeth, because little change occurs to the horizontal positions of the pulp horns or root canal orifices 22) . In clinical practice, however, severe secondary dentin formation on the side walls of the pulp chamber means that the root canal orifices are often covered with secondary dentin, identification of canal orifice potentially difficult 23) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using cone‐beam computed tomography evaluated traditional and conservative access; it concluded that traditional access requires the removal of 9.61 mm 2 of tissue for males and 8.91 mm 2 for females, and conservative access made the removal of 3.4 mm 2 for males and 3.1 mm 2 for females. Therefore, conservative access results in significantly less structure removal 35 . The controversy between traditional and conservative access relies on whether the clinician completely removes the pulp with conservative access; but this is also related to the skill of the clinician, tooth anatomy, and materials and methods utilized to open the access, clean, shape and obturate the root canal 36–38 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, conservative access results in significantly less structure removal. 35 The controversy between traditional and conservative access relies on whether the clinician completely removes the pulp with conservative access; but this is also related to the skill of the clinician, tooth anatomy, and materials and methods utilized to open the access, clean, shape and obturate the root canal. [36][37][38] The literature offers several successful cases reporting conservative endodontic accesses for anterior and posterior natural teeth and crowns.…”
Section: Discussionmentioning
confidence: 99%